Extending role by Japanese pharmacists after training for performing vital signs monitoring - Hasegawa F; Hazama K; Ikeda S; Takeda H (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: In Japan, the circumstances in which pharmacists work are changing. Pharmacists are expected to assess conditions of patients subject to medication to ensure proper use of pharmaceutical products. To ensure fulfilment of these roles, there have already been pharmacists' efforts in performing vital signs monitoring. Objective: To clarify the necessity and related issues, by investigating the state of vital sign monitoring in clinical field by pharmacists who have been trained in vital sign monitoring. Method: A web survey was conducted from 4th October to 3rd December 2012, subjecting 1,026 pharmacists who completed the vital signs training hosted by The Japanese Association of Home Care Pharmacies (JAHCP). Survey items were 1) basic information of a respondent, 2) situation of homecare conducted by pharmacists, 3) seminar attendance status, and 4) vital signs monitoring status after the seminar. Results: The number of valid respondents was 430 and the response rate was 41.9%. As a result of the present research, it was revealed that 168 pharmacists (41.4%), had the opportunity to perform vital signs monitoring. By conducting vital sign monitoring, effects such as 1) improved motivation of pharmacists and better communication with patients, 2) proper use of medication, and 3) cost reduction were confirmed. Conclusion: Judging from the results of the survey, pharmacists can improve medication therapy for patients by attaining vital sign skills and conduct vital sign monitoring. Pharmacists who perform vital sign monitoring should share cases where they experienced positive patient outcomes.